Impact of Key Macroeconomic Variables on Movement of the Indian Stock Market with Reference to BSE Sensex - Tripathi, Ravindra; Singh, Anurag Bhadur; Singh, Priyanka Tandon (Indian Journal of Finance, 2016)
The stock market is the barometer of the Indian economy. It is the vital system of the financial system of any economy. It helps in mobilizing the savings from different sectors. Many researchers have conducted studies to find out the relationship between the Indian stock market and key macro economic variables such as IIP, FDI, exchange rate, FII, gold price, oil prices, and so forth. In this research paper, an attempt was made to explore the relationship between the Indian stock market represented by BSE Sensex (SnX) and key macroeconomic variables : index of industrial production (IIP), foreign direct investment (FDI), and wholesale price index (WPI) of the Indian economy using the regression model. Quarterly data was collected from 2002-2003 to 2012-2013 for all variables like BSE Sensex, IIP, FDI, and WPI using secondary sources. The research is both descriptive and empirical in nature. The findings showed that IIP is a significant predictor of BSE Sensex ; whereas, FDI and WPI were not found to be a significant predictor of the BSE Sensex.